Bedah Mikrografi Mohs - Mohamad Mimbar Topik; Muhammad Al Farisi (Jurnal Medika Nusantara, 2023)
Mohs micrographic surgery is a specialized form of skin cancer surgery that has the highest cure rates for several cutaneous malignancies. Certain skin cancers can have small extensions or ‘‘roots’’ that may be missed if an excised tumor is serially cross-sectioned in a ‘‘bread-loaf’’ fashion, commonly performed on excision specimens. The method of Mohs micrographic surgery is unique in that the dermatologist (Mohs surgeon) acts as both surgeon and pathologist, from the preoperative considerations until the reconstruction. Since Dr. Mohs’s initial work in the 1930s, the practice of Mohs micrographic surgery has become increasingly widespread among the dermatologic surgery community worldwide and is considered the treatment of choice for many common and uncommon cutaneous neoplasms. Mohs micrographic surgery spares the maximal amount of normal tissue and is a safe procedure with very few complications, most of them managed by Mohs surgeons in their offices. Mohs micrographic surgery is the standard of care for high risks basal cell carcinomas and cutaneous squamous cell carcinoma and is commonly and increasingly used for melanoma and other rare tumors with superior cure rates. This review better familiarizes the dermatologists with the technique, explains the difference between Mohs micrographic surgery and wide local excision, and discusses its main indications.